INTERNATIONAL ENERGY RESEARCH INFRASTRUCTURES: MAPPING THE GLOBAL LANDSCAPE OF ENERGY RIS (RISCAPE): Based on Finland Futures Research Centre’s contribution to the Horizon 2020 project European Research Infrastructures in the International Landscape (RISCAPE) - Stein Knudsen, Mikkel; Birmoser Ferreira-Aulu, Marianna; Shabanova-Danielyan, Elizaveta; Wang, Weiqing; Luukkanen, Jyrki; Kaivo-oja, Jari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2022)
This e-book is an expanded version of the Energy Domain Report originally written for the project European Research Infrastructures in the International Landscape (RISCAPE), funded by the European Union. The domain report is also available in a shorter version, as well as a single chapter in the consolidated common project report. The full project report by Asmi et al. (2019) is available at https://riscape.eu/riscape-report/ The book is structured into three main parts. First, a preface introduces the report and highlights the field of Research Infrastructures (RIs) in connection with Futures Research. RIs are facilities that provide resources and services for research communities to conduct research and foster innovation. Due to our long history of researching energy futures, Finland Futures Research Centre led the mapping process of energy RIs The second part of this e-book presents an expanded version of the RISCAPE Energy Domain Report with its mapping of international Energy Research Infrastructures. The final list of mapped international energy RIs contains 37 organizations. The third and last part of this e-book consists of a postface and discussion on methodological considerations that can be useful for conducting similar mapping analyses in the future.